File management system for civil and criminal cases in Barangay Barangay Mintal, Davao City (FMSCCB) - Paclibar, Sheina Vi Mangompit (2011)
The File Management System for Civil and Criminal Cases in Barangay:Barangay Mintal, Davao City (FMSCCCB) is a stand-alone File Management System developed specifically for managing files of cases filed in Barangay. It is designed for one user only, called the system administrator. The system administrator is able to add new complaint, view schedules for ongoing cases, search from previous and present cases, edit account, attach external file, and generate monthly report and other forms. The output forms are in Portable Document Format (.pdf) and are saved in logical file system of the user where the system created a folder named with case number. Using FMSCCCB will make keeping case files secure and searching from previous cases will be easier. This system is open for development. It is recommended that the function be enhanced,to make it user-friendly. Downloading files from the system itself can be added to the system. Search function can also be modified by removing categorizing and transforming it to searching similar to that of search engines.